Future impacts of climate change on sediment influx rate in hydropower reservoir using SWAT - Abdul Razad A.Z.; Shamsuddini S.H.; Setu A.; Mohd Sidek L. (IOP Publishing Ltd, 2023)
Climate change causes more frequent and intense rainfall events, leading to severe erosion in the catchment and sediment transferred into rivers and reservoirs. This study focus on long term sediment load in major rivers in Cameron Highlands and prediction of annual sediment inflow into Ringlet Reservoir from 2000 to 2030. Soil Water Assessment Tool (SWAT) is used as the simulation tool, utilising future gridded rainfall 2017 to 2030 under CCSM and future land use 2030. Future annual rainfall is minimum at 1551 mm (in 2030) and maximum at 3150 mm (in 2029). The future projected annual sediment load into Ringlet Reservoir from 2017 to 2030 is averaged at 354,013 m3/year, ranging from 216,981 to 461,886 m3/year. Comparing between the historical period of 2000 to 2016 and future projection (2017-2030), annual sediment load shows an increase of 12 %. To combat the increase sediment yield, catchment management such as erosion control plan, drainage and runoff control must be developed to minimise sediment yield and subsequent effect of high sediment load transport via rivers and drainage network. Published under licence by IOP Publishing Ltd.